Personality and Individual Differences in Leadership Behavior. Α Review - Stiliadi, Stella (Technium Business and Management, 2024)
The study of personality and individual variations in leadership conduct is an intricate and multifaceted domain that has attracted substantial interest in organizational psychology and leadership studies. This review examines the complex correlation between personality traits and individual variations and their effect on leadership conduct. It encompasses diverse aspects such as servant leadership, transformational leadership, and shared leadership, as well as the influence of gender and cultural factors. A thorough comprehension of the intricate aspects of personality and individual differences in leadership behavior is essential to understanding how these factors interact with different leadership styles, organizational contexts, and cultural dynamics. This abstract introduces the complex connection between personality and individual differences in influencing leadership behavior. It paves the way for a more thorough examination of the challenges and perspectives related to this relationship.